WHAT DRIVES FEMALE FARMERS’ PARTICIPATION IN OFF-FARM ACTIVITIES? THE CASE OF RURAL NIGERIA - Shehu, Abbas; Mahmood, Jadeera; Umar, Sulaiman (Applied Studies in Agribusiness and Commerce, 2025)
Women often lack access to productive resources such as land and capital in most developing countries. This forces them to take part in off-farm activities to augment their little farm income. This study investigated factors that affect the involvement of women farmers in different types of off-farm entrepreneurial livelihood activities in rural Bauchi state, Nigeria. A purposive sampling method was used in selecting three local government areas in the western agricultural zone of the state and a random sampling method was used in selecting ten wards. 5% registered women farmers in each selected ward, making 134 respondents. Semi-structured questionnaires were administered to women farmers in 2017. The results revealed that food processing, farm product sales, trading and tailoring are the major off-farm livelihood activities engaged in by rural female farmers. Logit regression results revealed, as expected, that different factors affect their involvement in various types of off-farm activities. Food processing and tailoring required relatively high start-up capital and access to electricity as an investment and the use of machines was needed. Thus, access to credit or remittances and to electricity increases the probability of being involved in these activities. The requirements of trading being lower and access to market increases the probability of being involved. Provision of extension services, rural credit facilitation programmes, rural electrification, road and market structure development are instruments that are appropriate to support women farmers' involvement in off-farm activities.